Susunan Horison Tanah Sawah pada Toposekuen Latosol Berbahan Induk Volkanik di Daerah Bogor – Jakarta - Teti Arabia; Sarwono Hardjowigeno; Sudarsono Sudarsono; Widiatmaka Widiatmaka; Nata Suharta (Fakultas Pertanian, Universitas Syiah Kuala, 2008)
The Sequence of Horizons of Paddy Soils in a Toposequence of Latosol on Volcanic Parent Materials in the Bogor – Jakarta AreaABSTRACT. The sequence of horizons of paddy soils is different from non paddy cultivated. The aim of the research were: (1) to study the sequence of horizons of paddy soils in a toposequence of Latosol on Volcanic materials in the Bogor – Jakarta Area; (2) to study the sequence of paddy cultivated intensity to sequence of horizons. Twelve pedons of different altitude (90 – 650 m above sea level) and different paddy cultivated intensity (0/year, 1/year, 2/year) were investigated sequence of horizons in the field. The result of the research showed that the horizons sequence, on non paddy cultivated soils consist of: tillage layers and the original soil layers. On 1x paddy/year consist of: plow pan layer, and iron/manganese/nodule Mn illuviation layer. On 2x paddy /year consist of: tillage layer of surface reduction, plow pan layer, Fe/Mn illuviation layer, and reduce subsurface layer.